Patterns and processes underlying genetic diversity in the Namaqua rock mouse Micaelamys namaquensis Smith, 1834 (Rodentia : Muridae) from southern Africa - Chimimba, Christian Timothy (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2010.